Change for the better... not to confuse: Critical comments on the reform of the book of Inheritance - Saavedra Velazco, Renzo (2014)
This article analyzes and discuss critically the bill which pretendsto reform the book of inheritance. Concentrating its analysis on two points, when and how the inheritance is transferred and the limits for transferring assets to third parties, the author points out the practical complications and errors incurred by that reform.